From ultrasound to artificial intelligence: a new era of the regional anesthesia - Ahıskalıoğlu, Ali; Yayık, Ahmet Murat; Karapınar, Yunus Emre; Tulgar, Serkan; Çiftçi, Bahadır (NLM (Medline), 2022)
Regional anesthesia has become popular in daily anesthesia practice in recent years.1, 2 The use of US-guided regional anesthesia (URA) has increased thanks to the advantages of the US rapidly, such as direct visualization of nerves, safety, and simplicity. While the experienced clinicians and expert anesthesiologists can easily define the anatomical structures on the ultrasound, the residents and the less experienced clinicians may have difficulty at the beginning of education.3, 4 Here, a novel term emerges, ‘regional anatomy,’ which plays an essential role in UR.
Keywords: Regional Anesthesia; Artificial Intelligence; Ultrasound